Present Scenario of M-Cell Targeting Ligands for Oral Mucosal Immunization - Saraf, Surendra; Jain, Shailesh; Sahoo, Rudra N.; Mallick, Subrata (Current Drug Targets, 2020)
The immune system plays an important role in the prevention of infection and forms the first line of defense against pathogen attack. Delivering of antigen through mucosal route may elicit mucosal immune system as the mucosal surface is the most common site of pathogen entry. Mucosal immune system will be capable to counter pathogen at mucosal surface. Oral mucosal immunization opens the ways to deliver antigens at gut-associated lymphoid tissue. This can elicit both local and systemic immune response. Mucosal vaccines are economical, highly accessible, non parenteral delivery and capacity to produce mass immunization at the time of pandemics. To deliver antigens on the mucosal surface of the gastrointestinal tract, the immune system relies on specialized epithelial cell i.e. Microfold (M)-cell. An approach to exploit the targeting specific receptors on M-cell for entry of antigens has made a breakthrough in vaccine development. In this review, various strategies have been discussed for the possible entry of antigens through M-cells and an approach to increase the uptake and efficacy of vaccines for oral mucosal immunization.
Keywords: MALT